2016
DOI: 10.1097/prs.0000000000002337
|View full text |Cite
|
Sign up to set email alerts
|

Early Detection of Lymphatic Disorder and Treatment for Lymphedema following Breast Cancer

Abstract: Therapeutic, IV.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
103
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 106 publications
(105 citation statements)
references
References 45 publications
2
103
0
Order By: Relevance
“…However, the C-SFTI is advantageous as it can be used to evaluate a patient even when preoperative data is not available. Because in our previous study, docetaxel therapy, axillary lymph node dissection, and radiation therapy were correlated with breast cancer-related lymphedema, the impacts of these factors on SFTI should be analyzed with multiple logistic regression analysis with greater number of patients to confirm the true usefulness of SFTI for detecting chronic lymphedema in future studies (Akita et al, 2016).…”
Section: R E Su Ltsmentioning
confidence: 96%
See 1 more Smart Citation
“…However, the C-SFTI is advantageous as it can be used to evaluate a patient even when preoperative data is not available. Because in our previous study, docetaxel therapy, axillary lymph node dissection, and radiation therapy were correlated with breast cancer-related lymphedema, the impacts of these factors on SFTI should be analyzed with multiple logistic regression analysis with greater number of patients to confirm the true usefulness of SFTI for detecting chronic lymphedema in future studies (Akita et al, 2016).…”
Section: R E Su Ltsmentioning
confidence: 96%
“…The lymphatic function of each patient was categorized based on the findings of ICG lymphography. When typical lymphatic dysfunction with a stardust or diffuse pattern was observed, the limb was considered to have lymphatic dysfunction, and instructions about self-therapy techniques, such as skin care, exercise, elevation, and compression garment use, were provided as described in the Best Practice for the Management of Lymphoedema by Lymphoedema Framework (Akita et al, 2013(Akita et al, , 2016Lymphoedema Framework, 2006;Ogata, Azuma, Kikuchi, Koshima, & Morimoto, 2007;Unno et al, 2007;Yamamoto et al, 2011). Pantyhose-type compression garment was recommended to all patients with lower extremity dysfunction.…”
Section: P a Ti E Nt S A Nd M E Th Odsmentioning
confidence: 99%
“…14 Pathophysiologic features of UEL are different from those of LEL and seem to follow a less aggressive course. 34 Early evaluation using ICG-L after breast cancer treatment has shown that the number of patients with splash pattern that improve to a linear pattern are higher compared with the lower limb (37.5 vs. 16%). 33,34 Interestingly, even patients with stardust pattern may improve to linear (20.6%) or splash (10.3%) patterns after conservative treatment.…”
Section: Lower Extremity Lymphedemamentioning
confidence: 99%
“…Patients who were candidates for surgical treatment for BCRL first underwent examination of lymphatic function by indocyanine green (ICG) lymphography. The findings were categorized into linear, splash, stardust, diffuse, or no flow, as previously reported [14][15][16][17] : when only linear and splash patterns were observed, the patient was diagnosed with subclinical lymphedema and did not undergo any treatment; patients with stardust pattern and diffuse pattern (dermal back flow [DBF] patterns) were diagnosed with chronic lymphedema, and when no flow was observed and less than a year had passed since the breast surgery, the patient was diagnosed with temporary residual lymphatic dysfunction following breast cancer treatment.…”
Section: Subjectsmentioning
confidence: 99%